Phosphatase Producing Microbes Associated with Fish and Shellfish in Trivandrum Coast - Eapen, Alex; K., Maya; K., Dhevendran; P., Natarajan (Fishery Technology, 2025)
Total heterotrophic bacteria and fungi and the phosphatase producing bacteria and fungi in the gill, guts and muscle of fish (Etroplus spp., Gerres sp. and Glossogobius sp.) and viscera and mantle of shellfish (Vellorita sp. and Perna sp.) were studied. The hydrographic parameters of the environment from where the fishes were caught were also studied. Except shellfish Perna indica, all the species studied harboured phosphatase producing bacteria. The gut portion of finfish contained high amount of total heterotrophic as well as phosphatase producing bacteria. The present study showed that the phosphatase producing bacteria mainly belonged to Bacillus, Vibrio, Micrococcus and Corynebacterium spp. Moraxella showed maximum growth at 5% salt concentration. Moraxella and Aeromonas were sensitive towards mercury while 45% of Vibrio showed growth at 0.4 ppm mercury.